2012
DOI: 10.1074/jbc.m111.333120
|View full text |Cite
|
Sign up to set email alerts
|

Serine Hydroxymethyltransferase Anchors de Novo Thymidylate Synthesis Pathway to Nuclear Lamina for DNA Synthesis

Abstract: The de novo thymidylate biosynthetic pathway in mammalian cells translocates to the nucleus for DNA replication and repair and consists of the enzymes serine hydroxymethyltransferase 1 and 2α (SHMT1 and SHMT2α), thymidylate synthase, and dihydrofolate reductase. In this study, we demonstrate that this pathway forms a multienzyme complex that is associated with the nuclear lamina. SHMT1 or SHMT2α is required for co-localization of dihydrofolate reductase, SHMT, and thymidylate synthase to the nuclear lamina, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
150
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(154 citation statements)
references
References 43 publications
(73 reference statements)
4
150
0
Order By: Relevance
“…4 E and F). SHMT1 is an essential scaffold protein for assembly of the nuclear de novo dTMP biosynthesis complex (12). Cells cultured in folate-depleted medium and 1 μM As 2 O 3 , alone or in combination, resulted in an increase in DNA damage, as measured by phosphorylated histone H2AX (γH2AX) immunostaining in HeLa cells (Fig.…”
Section: Mthfd1mentioning
confidence: 99%
See 2 more Smart Citations
“…4 E and F). SHMT1 is an essential scaffold protein for assembly of the nuclear de novo dTMP biosynthesis complex (12). Cells cultured in folate-depleted medium and 1 μM As 2 O 3 , alone or in combination, resulted in an increase in DNA damage, as measured by phosphorylated histone H2AX (γH2AX) immunostaining in HeLa cells (Fig.…”
Section: Mthfd1mentioning
confidence: 99%
“…5,10-methyleneTHF can be regenerated either from serine and THF through the activity of serine hydroxymethyltransferase (SHMT1 or SHMT2α) or from formate, ATP, NADPH, and THF by the activity of methylenetetrahydrofolate dehydrogenase 1 (MTHFD1) (4)(5)(6). SHMT1, DHFR, and TYMS are small ubiquitin-like modifier (SUMO)-ylated and translocate to the nucleus at the G1/S boundary (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). During S-phase of the cell cycle, the nuclear de novo dTMP synthesis pathway assembles as a lamin-associated multienzyme complex that consists of SHMT, MTHFD1, TYMS, DHFR, and other components of the replication machinery (12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Serine and glycine synthesis is accompanied by the production of GSH, a tripeptide that is comprised of glycine, glutamate and cysteine, contributing to the redox balance in cells as reactive oxygen species (ROS) scavenger [20][21][22][23]. Serine and glycine are also involved in nucleotide synthesis, thus entering into one-carbon metabolism and promoting cancer cell proliferation [14,18,24]. It was reported recently that, upon serine starvation, p53 activates p21 to promote GSH production to combat ROS [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…17 In addition, the enzymes of de novo thymidylate synthesis pathway form a scaffolded multienzyme complex at replication sites in the nucleus. 18 These studies demonstrated that site-specific synthesis of dNTPs provides an efficient way to ensure sufficient building blocks for DNA synthesis during repair and replication. In this study, we present evidence that CMPK forms a complex with Tip60/RNR, and is recruited to DNA damage sites.…”
Section: Introductionmentioning
confidence: 99%